KONTRIBUSI KOMPETENSI PROFESIONAL TERHADAP KINERJA MENGAJAR GURU RAUDHATUL ATHFAL SE-KECAMATAN SUKUN - Intan Febry Minofa Fitri; Eko Setiawan; Ika Anggraheni (UNISMA, 2022)
Education is an effort to grow the potential of every human being to become a good human being. One component of education is the teacher. Teachers play an important and main role in the continuity of learning for students, so teachers are very influential in the creation of quality educational processes and outcomes. In carrying out their duties, roles and functions, teachers are required to have competency standards that must be met, one of which is professional competence. This study aims to describe the characteristics of the professional competence of Raudhatul Athfal teachers in the Sukun District and the contribution of professional competence to the teaching performance of Raudhatul Athfal in the Sukun District. This study uses a quantitative approach with a survey method with a population / sample of all Raudhatul Athfal teachers in the Sukun District. Data collection techniques were carried out by distributing questionnaires/questionnaires. The results showed the results of the analysis of the hypothesis that the significance value was 0.000 <0.005 so that Ho was rejected and Ha was accepted which meant that there was a contribution of professional competence to the teaching performance of teachers.